Standardization of the Multicultural State-Trait Anger Expression Inventory in university students - Ugarriza Chávez, Nelly (1998)
Percentile rank and normalized T standard scores related to the Multicultural State-Trait Anger Expression Inventory (IMECH) are presented. Obtained from a sample of 1502 freshman students of a public and a private university of Lima-Perú. The Alpha Cronbach reveals strong internal consistency of the Scale (IMECH). The correlations among the variables studied using the varimax rotation allows to find three factors: Factor I related to trait anger, anger in and anger out (factorial load >. 53). Factor II set the relatíon among anger stale and trait anxiety (factorial load >. 59). Factor III reveals The relationship among angry expressed behavioraly and cognitively (factorial load > .80). The depression diverges from the other principal constructs, the factorial loadings are low and show no relationship with none of the three factors.